Effects of Regional Stress State and Pore Fluid Pressure on the Onset and Style of Caldera Collapse - Jara-Munoz, P (John Wiley and Sons Inc, 2025)
Collapse calderas result from subsidence of a magma reservoir roof during large-volume eruptions. Whilst calderas form in various tectonic settings, it is unclear how regional (“far-field”) forces influence caldera fault nucleation, orientation and architecture. Furthermore, although the presence of a pore fluid is known to reduce the effective stress, it is typically neglected in past caldera collapse models. Utilizing two-dimensional Distinct Element Method (DEM) models, we explore the influences of regional stress and pore fluid pressure on the evolutions of stress, strain and faulting during caldera subsidence. We simulate a shallow magma volume as an inviscid inclusion within a homogeneous crust and decrease the inclusion s pressure to model magma withdrawal. Results reveal that the critical underpressure needed to trigger collapse is reduced in extensional regimes, particularly in fluid-saturated conditions, due to lowered frictional resistance on faults. We observe three progressive deformation stages: initial fracturing at the reservoir roof, collapse onset, and complete roof failure. The geometry of faults depends on the tectonic setting, with extensional conditions favoring steeper fault dips and compressional settings promoting shallower, outward-dipping reverse faults. Models simulating a fluid-saturated crust exhibit similar effects to those models that simulate lower strength materials. This study highlights the need to account for regional stress states and crustal properties in volcanic hazard assessment, especially in caldera systems with complex hydrothermal or tectonic influences. Our findings are compared with recent collapse episodes, underscoring the utility of DEM modeling in understanding crustal responses to magma depletion. © 2025. The Author(s).